Gamma-ray spectrometry signature of paraná volcanic rocks: Preliminary results - Nardy, Antonio José Ranalli [UNESP]; Moreira, César Augusto [UNESP]; Machado, Fábio Braz; Luchetti, Ana Carolina F. [UNESP]; Hansen, Marco Antonio Fontoura; Rossini, Adílson José [UNESP]; Barbosa, Vladimir [UNESP] (My University, 2014)
The Paraná volcanic rocks (Serra Geral Formation) are characterized by four different types of rocks. The basalts are the most common, and display an integranular texture and dark gray to black color, in massive outcrops. The acid volcanics are represented by aphyric, salt-and-pepper texture, light gray color, named Palmas type (ATP), and by strongly porphyritic, green to brownish gray color, named Chapecó (ATC). The intermediate rocks are represented by light gray, aphyric andesites. Sometimes, it is very difficult to distinguish andesites from ATP rocks or even from basalts, using only petrographic criteria. However, from the geochemical point of view, these rocks are quite different, including the radioactive elements (K, U and Th). In this way the portable gamma-ray spectrometer argued being a useful tool to recognize different rock types with different total gamma-ray signature, such as basalts (4.7 ± 0.8 μRh-1); andesites (7.2 ±1.2 μRh-1), ATC (11.3 ± 1.2 μRh-1) and for ATP (15.4 ± 2.4 μRh-1).
Keywords: Gamma-ray spectrometry; Paraná Magmatic Province; Serra geral formation; Volcanic rocks